Efficacy of Parenteral Amantadine Therapy in the Treatment of Multiple System Atrophy With Predominant Parkinsonism. Issue 5 (September 2018) - Friedberg, Adit; Erikh, Ilana; Nassar, Maria; Sprecher, Elliot; Schlesinger, Ilana
Abstract : Objective: The aim of this study was to assess clinical response to a high-dose intravenous (IV) amantadine given for 5 consecutive days in patients with multiple system atrophy parkinsonism (MSA-P). Methods: Subjects with a diagnosis of MSA-P treated with IV amantadine were included. Patients' disease severity before and after therapy was evaluated using the Unified Multiple System Atrophy Rating Scale (UMSARS). Results: Fourteen subjects (8 females) were included. In 10 subjects (71.4%), clinical improvement was noted. The UMSARS score after treatment decreased by 2 points (median [interquartile range, 0–3]) when compared with UMSARS score at baseline ( P = 0.0020). Upon examining the walking parameter, a trend of improvement was shown ( P = 0.0625) (range, 0–1 points). Neither specific demographic parameters nor occurrence of adverse effects was found to be a predictive factor for improvement. Adverse events were mild and transient except for one patient who experienced acute psychosis prompting treatment cessation, upon which psychosis resolved. Conclusions: Our preliminary data show that IV amantadine may be a safe and effective therapy in MSA-P. A double-blind placebo-controlled trial is needed to establish the true benefit of amantadine therapy.